Ultrasonic ovarian status in summer anestrus postpartum Murrah buffaloes - ROHILIA, NAVNEET; SINGH, UMED; SHARMA, R K; SINGH, INDERJEET (The Indian Journal of Animal Reproduction, 2023)
The present investigation was aimed to diagnose the ovanan status in postpartum anestrus buffaloes during summer byultrasonography. Twelve parous lactating, suckled Murrah buffaloes (Buba/us bubalis) 64-180 days postpartum (1st to 3rdlactation) were included in the study. Ovarian follicular changes were monitored with a real time B-mode ultrasound scannerusing frequency of 7 .0 MHz on day O (first day of scanning), 6, 8 and day 10. Ultrasonographic scanning of ouaries at W day~interval clearly revealed the presence of CL in three animals (25% ). The average number of small ( 9 mm diameter) and total follicles in both ov~es ranged from 4.8 to 5.3, 2.2 to 2.4, 0.6 to 0.8 and 7.7to 8.3, respectively. Six of the remaining nine animals had at least one large follicle(> 9 mm diameter) in growing phase from day6 to day 10. The remaining three animals had the largest follicles of< 9 mm in diameter on day 10. Similarly, overall largestfollicle mean diameter ranged from 9.7 to 10.5 mm. In conclusion, anestrus condition occurs due to failure of ovulation, ratherthan failure of development of dominant follicle, as revealed in summer anestrus postpartum buffaloes except sub estrusanimals. Therefore, comprehensive study of ovarian follicular turnover and related endocrine profiles is required in order tounderstand the physiology of summer acyclicity in buffaloes and in turn, its judicious management.
Keywords: Murrah buffaloes; anestrus; postpartum